Pengaruh Metode Mind Mapping Berbantu Gawai Terhadap Pemahaman Nilai-Nilai Pancasila Pada Siswa Kelas VI SD - Muhammad Mutofifin; Su'ad Su'ad; Wawan Shokib Rondli (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of the gadget-assisted Mind Mapping method on the understanding of Pancasila values in sixth grade elementary school students in the Sunan Kalijaga Gugus Guntur Demak. This study uses the True Experimental Design method in the form of Pretest-Posttest Control Group Design. The research was carried out in the Sunan Kalijaga Cluster, Guntur District, Demak Regency, 2 elementary schools were taken by random sampling from a population of 9 elementary schools. The sample consisted of SDN Sidokumpul consisting of 18 students (control class) and SDN Gaji 2 consisting of 20 students (experimental class). The instrument used is a multiple choice test. The results showed that there was an influence of the Mind Mapping method on the understanding of Pancasila values in sixth grade elementary school students in the Sunan Kalijaga Gugus Guntur Demak. This is evident from the results of the t test with the value of Sig. (Two-Sided p) of 0.002, then 0.002 <0.05. So Ha is accepted, and Ho is rejected.